Analyzing longitudinal patterns of river metabolism in five distinct rivers - Schmer, Natalie K., author; Ross, Matthew R. V., advisor; Wrighton, Kelly C., committee member; Covino, Tim P., committee member (Colorado State University. Libraries, 2021)
The River Continuum and Serial Discontinuity Concepts are two common frameworks or theories to describe river ecosystem structure and function. While these concepts help explain how rivers should behave, the reality is that aquatic ecosystems are being changed and degraded due to dams which regulate flow and changes to land use and land cover that can negatively impact aquatic ecosystems. Ecosystem metabolism is an increasingly common way to monitor and assess river health and functioning. This analysis is a data synthesis to examine longitudinal coherence in productivity patterns and identify the strongest controls that disrupt coherence. I find that between discharge, dissolved oxygen, and metabolism, metabolism is the least predictable variable going downstream regardless of land use and river characteristics, but at the same time did show patterns consistent with the expected patterns of the River Continuum Concept or other theories of river function variation. This lack of coherence and predictability in river metabolism across sites within rivers highlights effects monitoring methods, river-specific characteristics, and the overall lack of satisfactory theories for how larger rivers behave, despite an abundance of riverine theories.